2018
DOI: 10.4314/as.v16i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of adoption level of risk management strategies by fish farmers in Degema Local Government Area of Rivers State, Nigeria

Abstract: The study examined the socio-economic determinants of level of adoption of risk management strategies by fish farmers in Degema Local Government Area of Rivers State. The study specifically described the socioeconomic characteristics of fish farmers, identified the various sources of risk and determined the socioeconomic factors that influence the level of adoption of risk management strategies. A two-stage sampling technique was used to select sixty-seven (67) fish farmers. Structured questionnaire and interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
(4 reference statements)
5
2
0
Order By: Relevance
“…The negative effects of age may be due to younger farmers being technology savvy which helps to adopt to different risk management strategies. This is in line with the findings of Ugwuja et al (2017) who reported that younger farmers adopted more risk management strategies in fish farming. Marital status (X 3 ) was significant at 5% and has positive coefficient.…”
Section: Socio-economic Factors In Level Of Adoption Of Risk Management Strategies In E-bankingsupporting
confidence: 92%
“…The negative effects of age may be due to younger farmers being technology savvy which helps to adopt to different risk management strategies. This is in line with the findings of Ugwuja et al (2017) who reported that younger farmers adopted more risk management strategies in fish farming. Marital status (X 3 ) was significant at 5% and has positive coefficient.…”
Section: Socio-economic Factors In Level Of Adoption Of Risk Management Strategies In E-bankingsupporting
confidence: 92%
“…The mean years of experience of about 11 years implies that the catfish farmers have a better understanding of the dynamics of catfish production in terms of price, market information and risk coping in the study area. This result is in accordance with the reports of [8] and [15] that longer years of experience enable catfish farmers to possess good skills, better strategies to fish farming business, able to predict market situation for higher sales, take cognizance of the risk situation as well as their adaptive mechanisms. Only 29.8% of the respondents engaged in catfish farming on full time basis.…”
Section: B Catfish Farming Activities Of the Respondentssupporting
confidence: 90%
“…Married farmers are obligated to provide for their family members and this impels them to reduce their risks level and be more productive than unmarried farmers. This result is in tandem with the findings of [8] that majority of the catfish farmers in Degema LGA of Rivers State were married and that married farmers were more committed to their business as they are responsible to meeting their family needs. Also, majority (64.9%) of the respondents had 5 people or less in their household.…”
Section: A Socio-economic Characteristics Of the Respondentssupporting
confidence: 78%
See 1 more Smart Citation
“…The mean household size and years in farming were 5 and about 8 respectively. On household size, and years in farming, Ugwuja et al (2017) and Ogunmefun and Achike (2017) respectively reported a similar outcome. The mean religion, credit access, gender, rearing system, and stock size were respectively 0.679, 0.400, 0.671, 0.636, and 22386.430.…”
Section: Resultsmentioning
confidence: 72%